IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH (MBS) DALAM MENINGKATKAN MUTU LULUSAN DI SMK GLOBAL MARINE JATISARI KABUPATEN KARAWANG - Nunung Darwati (UNISAN JURNAL, 2024)
School Based Management (SBM) is essentially a recognition that the educational process will not run well if everything is controlled from the center. The aim of this research is to determine the implementation of School Based Management (MBS) in improving the quality of graduates at Global Marine Jatisari Vocational School, Karawang Regency. This research uses data collection techniques using interview methods, observation methods and documentation methods. The data validity technique in this research is triangulation with data analysis with data reduction stages, data presentation and drawing conclusions. The process of improving the quality of graduates goes through stages (1) The planning carried out includes preparing the education unit curriculum, preparing student programs, preparing school work plans which include 8 education management standards. (2) In the organizing stage of Global Marine Jatisari Vocational School, Karawang Regency, create a school organizational structure, dividing teaching tasks and additional tasks with details of each task. (3) In the implementation stage of improving the quality of graduates, the focus is on optimizing teaching and learning activities with efforts to include infrastructure, learning tools consisting of curriculum, Annual Program, Semester Program, Syllabus and RPP as well as teachers’ abilities in managing learning and administering school exams in an orderly manner. and directed.